NFκB is an Essential Intermediate in the Activation of Endothelial Cells by Anti-β2-Glycoprotein 1 Antibodies - Dunoyer-Geindre, Sylvie; de Moerloose, Philippe; Galve-de Rochemonteix, Béatrix; Reber, Guido; Kruithof, Egbert K. O. (Thrombosis and Haemostasis, 2002)
Antiphospholipid antibodies (aPLA) are associated with thrombophilia and recurrent pregnancy loss. They bind directly to anionic phospholipids or via phospholipid-binding proteins such as β2-glycoprotein 1 (β2GP1). The underlying mechanisms by which aPLA induce a thrombophilic phenotype are not well understood.The present work was done to determine whether antibodies to β2GP1 activate endothelial cells (EC) and whether NFκB is involved in this activation. Incubation of EC with these antibodies resulted in a redistribution of NFκB from the cytoplasm to the nucleus after a delay of several hours. This was accompanied by an increased expression of tissue factor and of the leukocyte adhesion molecules ICAM-1, VCAM-1 and E-selectin. Inhibition of the nuclear translocation of NFκB abolished the response to these antibodies. In comparison to anti-β2GP1 antibodies, incubation of EC with TNF resulted in a more rapid (within 30 minutes) redistribution of NFκB and a more pronounced expression of tissue factor and of the leukocyte adhesion molecules. The slower response to the antibodies as compared to TNF suggests that the NFκB response to anti-β2GP1 antibodies is indirect.Taken together our results imply that NFκB is an essential intermediate in the activation of EC by anti-β2GP1 antibodies.
Keywords: β2-glycoproteins; endothelial cells; NFκB; adhesion molecules; tissue factor